Auditory evoked potentials in a newborn Wistar rat model of hyperbilirubinemia - Gökdogan,Çagil (2016)
ABSTRACT INTRODUCTION: Hyperbilirubinemia is a common health problem in newborns. Its effects can be different according to the level and duration of the hyperbilirubinemia. The toxic effect of bilirubin on the auditory system can be seen as a sensory neural hearing loss or auditory neuropathy spectrum disorder (ANSD). OBJECTIVE: The purpose of our study was to determine the effects of toxic bilirubin level on the auditory system by using Auditory Brainstem Response audiometry. METHODS: Rats are used as animal models due to their low cost and easy attainability. Auditory Brainstem Response was used for auditory assessment. In this study, three groups were established: experimental, control and placebo groups. RESULTS: In the experimental group, which consists of rats with hyperbilirubinemia, sensory neural hearing loss was found bilaterally in 4 rats (66.67%) and unilaterally in 2 rats (16.67%) and auditory neuropathy spectrum disorder was found unilaterally in 1 rat (8.33%). Auditory Brainstem Response thresholds were significantly elevated compared to control and placebo groups (p < 0.05). CONCLUSION: Hyperbilirubinemia of newborn rats may result both in sensory neural hearing loss and auditory neuropathy spectrum disorder.